Pengaruh Komunikasi Interpersonal, Resiliensi, dan Locus of Control terhadap Kesiapan Belajar Mandiri Mahasiswa SI UIN Jakarta - Arrobbani, Abdul Aziz; Fadilla, Aqsyal Hilmi; Rif'at, Desriszka; Nurmianti, Evy (Journal of Society Bridge, 2026)
Technology is changing quickly, and the way students learn in college is also shifting. Therefore, students must be able to study independently. The ability to study independently depends not only on clear thinking, but also on your feelings and how you interact with others. This study looks at how good communication with others, how people see control in their lives, and how well they handle difficulties affect their ability to learn on their own. To do this, we used a survey with questions given to college students. We then used math tools to look at how these things are connected. The results should help us understand what helps students be better at learning on their own and give schools ideas on how to create better learning plans. The results show that interpersonal communication, locus of control, and resilience have a significant positive effect on students’ self-directed learning readiness, with resilience showing the strongest influence.